Optimalisasi Manufacturing Cycle Effectivieness (MCE) terhadap Pengelolaan Value Added Activities dan Non Value Added Activities dalam Meningkatkan Efisiensi Produksi - Indah Purnamasari; Doddy Adhimursandi; Maryam Nadir (Fakultas Ekonomi Dan Bisnis Universitas Mulawarman, 2018)
The aim of this study is to recognize the effectiveness and to optimize management of value and non-value added activities in increasing the production efficiency at a coal mining company PT Gading Jaya Perkasa. The production activities are value added activities, which is a production process, and non-value added activities including inspection time, waiting time and money time. The research method is Manufacturing Cycle Effectiveness (MCE). Data collection is done by observation interview, analyzing documentation and literature study. Data analysis technique is qualitative with descriptive analysis. The results of this study with manufacturing cycle effectiveness (MCE) calculation that have been done are 60,81% in April, 61,57% in May and 49,75% in June. The achievement level of the company’s productivity and efficiency has been quite good with the production achievements 98,43 ton/hour in April, 100 ton/hour in May and 79,67 ton/hour in June. The production efficiency is 88%. The MCE calculation can be utilized by PT Gading Jaya Perkasa management to plan the reduction of non-value added activities for continuous improvement. By using MCE method, production and cost effectiveness can be attained optimally